Актуалізація концепції веб-сайту Львівської політехніки: адаптивний дизайн та розподілене управління інформаційним наповненням - Березко, Олександр; Жежнич, Павло; Зуб, Христина; Ковалик, Лілія; Berezko, Oleksandr; Zhezhnych, Pavlo; Zub, Khrystyna; Kovalyk, Liliya (Видавництво Львівської політехніки, 2017)
У статті обґрунтовано важливість адаптивного дизайну для веб-сайтів університетів та описано актуалізацію концепції веб-сайта Львівської політехніки з цього погляду, а також новий розподілений підхід до управління інформаційним наповненням.

The work proves the importance of responsive web design for university websites and describes such a design using the new website of Lviv Polytechnic National University case study. General approaches that were used aim to satisfy the demands of webmasters and content managers as well as website visitors. The paper presents the key tools of web site construction with distributed approach to manage content. We considered usage patterns according to main specifics of modern devices to ensure the site to be configured properly and viewable.
Actualization of the concept of the website of Lviv polytechnic national university: responsive design and distributed management of content
Keywords: веб-сайт; адаптивний дизайн; використовуваність; веб-розробка; університет; website; responsive web design; usability; web development; university; 004.738.5